Bridging Pesantren Pedagogy and Digital Assessment through Wordwall Gamification: A Hybrid Model for Arabic Language Learning - Achmad Farouq Abdullah; Sofwan Manaf; Tutik Lestari (Educazione: Journal of Education and Learning, 2025)
This study aims to test the effectiveness of Wordwall gamification within the Hybrid Evaluation Model for Arabic language learning at the Rafah Bogor Islamic Boarding School, as a dissemination of the Durusullughah 4.0 innovation based on Problem-Based Learning (PBL) that was previously developed. Using a quantitative approach with a quasi-experimental, nonequivalent control group design, this study involved 60 students of class I TMI, divided into experimental groups (n=30) who received Wordwall-PBL-based learning and control groups (n=30) who used conventional methods. The instrument is an Arabic-language competency test (mufrodat and qawa’id) that has been validated with an alpha coefficient (α) of 0.84. The results of the Independent Samples t-test analysis showed a significant difference between the two groups (t (58) =5.812, p<0.001), with the average posttest score of the experimental group (M=81.23; SD=6.41) significantly higher than that of the control group (M=70.87; SD=7.54). The N-Gain Score of the experimental group was 0.65 (moderate-high category) compared to 0.36 in the control group. The perceptions of students and teachers towards the media showed very high acceptance rates (86.9% and 89%, respectively). These findings confirm that the PBL Wordwall model can be effectively disseminated in other Islamic boarding schools and strengthen Arabic language learning without compromising the typical values of Islamic boarding schools.